2019
DOI: 10.1007/s40368-019-00458-0
|View full text |Cite
|
Sign up to set email alerts
|

Impact of soft drinks to health and economy: a critical review

Abstract: Aims To provide information regarding the different types of soft drinks and critically reviewing their risk on the dental and general health of children and adolescents, as well as the cost associated with such drinks. Methods The literature was reviewed using electronic databases, Medline, Embase, Cochrane library, and was complemented by cross-referencing using published references list from reviewed articles. Search words; soft drinks, juices, carbonated drinks, sports and energy drinks, soft drink and den… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
71
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(74 citation statements)
references
References 56 publications
1
71
0
2
Order By: Relevance
“…Consumption of soft drinks, such as sodas and packaged juices, has increased among children and adolescents in the last decades. This constitutes not only a problem for oral health, but also for health in general, both because of its high sugar content and low pH [46]. Therefore, parental and patient education regarding the harmful effects of these drinks is necessary.…”
Section: Discussionmentioning
confidence: 99%
“…Consumption of soft drinks, such as sodas and packaged juices, has increased among children and adolescents in the last decades. This constitutes not only a problem for oral health, but also for health in general, both because of its high sugar content and low pH [46]. Therefore, parental and patient education regarding the harmful effects of these drinks is necessary.…”
Section: Discussionmentioning
confidence: 99%
“…Diet-related risk factors, including obesity/overweight, have been associated with some non-communicable diseases such as cardiovascular diseases, diabetes mellitus and certain cancers. One of the main problems in the modern diet is the consumption of excessive amounts of sugar [1]. Term total sugars include all mono-and disaccharides, while free and added sugars exclude naturally occurring sugars in milk, fruit, and vegetables.…”
Section: Introductionmentioning
confidence: 99%
“…However, reducing the amount of sugar in beverages can have a negative impact on sensory perception, affecting product sales. Many manufacturers therefore offer beverages with low and no-calorie sweeteners (LNCS) [1].…”
Section: Introductionmentioning
confidence: 99%
“…It is vital for health authorities to take these findings into consideration when designing strategies to improve diet quality among individuals with depression. Although this research showed that the number of people who never or hardly ever consumed legumes and people who consumed soft drinks with sugar on a daily basis declined from 2011 to 2017, government agencies should persevere with their efforts to reduce the consumption of soft drinks with sugar due to its potential dangers for general health [117] and encourage people to consume more legumes for their health benefits [111]. Additionally, our findings of depressive people suggest that males, people aged 16-24 years old and 25-44 years, separated or divorced, and also smokers were more likely to have a poor or improvable diet quality.…”
Section: Implications For Research and Practicementioning
confidence: 80%